Impact of feedstocks and downstream processing technologies on the economics of caproic acid production in fermentation by Megasphaera elsdenii T81. (April 2020) - Kim, Hyunjin; Choi, Okkyoung; Jeon, Byoung Seung; Choe, Woo-Seok; Sang, Byoung-In
Graphical abstract: Highlights: Caproic acid was produced from the hydrolysate of Jerusalem artichoke (JA). Megasphaera elsdenii T81 utilized fructose and glucose in the hydrolysate of JA. The hydrolysate of JA increased carbon consumption and caproic acid production. Value-added chemical production using inexpensive feedstocks was evaluated. Abstract: Caproic acid (CA) was produced by Megasphaera elsdenii T81 with Jerusalem artichoke tubers (JA) as a feedstock. More CA was produced under the medium with the acid hydrolysate of JA than the comparative medium with a carbon composition similar to that of JA. CA was produced up to 13.0 g/L and 0.52 g/L/h with extractive fermentation using a mixed solvent of alamine 336 in oleyl alcohol at 37 °C. The JA cost to produce 1 ton of CA is only 505 USD, which is much lower than that required for purchasing sucrose (860 USD) in CA production. As a result of the analysis performed using SuperPro Designer, including the cost of distillation to obtain pure CA, the estimated production cost for CA from dry JA is 1869 USD/ton CA at the production scale of 2000 ton/year, which is lower than the current market price for petroleum-derived CA (~2500 USD/ton).